Structure-Based Drug Design in Medicinal Chemistry: The Devil is in the Detail - Kuhnert, Maren; Diederich, Wibke E. (Synlett, 2016)
Structure-based drug design (SBDD) has become an important concept in medicinal chemistry, and the hypothesis that similar ligands bind in a similar fashion is widely accepted within the medicinal chemistry community. However, there are a number of interesting case studies, some of which are discussed in detail, which highlight that this does not hold true on a comprehensive basis.
Keywords: medicinal chemistry; structure-based drug design; hit-to-lead optimization; drug development; X-ray crystallography